Analysis Inventory of Consumable Goods Using Min-Max Method at Universitas Pertamina - Nurma Irfan Romadhon; Iwan Sukarno; Mirna Lusiani (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2022)
Inventory control is one of the problems faced by Universitas Pertamina. In the management of inventory, especially Consumable items, Universitas Pertamina does not determine the limited value of inventory that must be stored. Thus, this causes asset management difficult to determine the ordering quantity for each item and how many items should be stored in the warehouse. The purpose of this study is to recommend policies related to the value of safety stock, minimum stock, and maximum stock for each consumable item. The method used is the Min-Max Stock method. In addition, the ABC classification method is also used to classify items based on the level of usage. The results of this study are in the form of value limits for safety stock, minimum stock, and maximum stock. Then the priority item classification must be managed. Based on the calculation results, it is found that by using the min-max method, Universitas Pertamina can save up to 30% of inventory costs compared to the current policy.